Silkomics: Insight into the Silk Spinning Process of Spiders - Dos Santos-Pinto, José Roberto Aparecido [UNESP]; Garcia, Ana Maria Caviquioli [UNESP]; Arcuri, Helen Andrade [UNESP]; Esteves, Franciele Grego [UNESP]; Salles, Heliana Clara [UNESP]; Lubec, Gert; Palma, Mario Sergio [UNESP] (American Chemical Society (ACS), 2016)
The proteins from the silk-producing glands were identified using both a bottom-up gel-based proteomic approach as well as from a shotgun proteomic approach. Additionally, the relationship between the functions of identified proteins and the spinning process was studied. A total of 125 proteins were identified in the major ampullate, 101 in the flagelliform, 77 in the aggregate, 75 in the tubuliform, 68 in the minor ampullate, and 23 in aciniform glands. On the basis of the functional classification using Gene Ontology, these proteins were organized into seven different groups according to their general function: (i) web silk proteins-spidroins, (ii) proteins related to the folding/conformation of spidroins, (iii) proteins that protect silk proteins from oxidative stress, (iv) proteins involved in fibrillar preservation of silks in the web, (v) proteins related to ion transport into and out of the glands during silk fiber spinning, (vi) proteins involved in prey capture and pre-digestion, and (vii) housekeeping proteins from all of the glands. Thus, a general mechanism of action for the identified proteins in the silk-producing glands from the Nephila clavipes spider was proposed; the current results also indicate that the webs play an active role in prey capture.
Keywords: bottom-up gel-based proteomic approach; Nephila clavipes; shotgun proteomic approach; silk proteins; silk-producing glands